Wear Prediction on Total Ankle Replacement Effect of Design Parameters - Saad, Amir Putra Bin Md.; Syahrom, Ardiyansyah; Harun, Muhamad Noor.; Kadir, Mohammed Rafiq Abdul; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book develops and analyses computational wear simulations of the total ankle replacement for the stance phase of gait cycle. The emphasis is put on the relevant design parameters. The book presents a model consisting of three components; tibial, bearing and talar representing their physiological functions.
Introduction -- Contact Pressure of Total Ankle Replacement -- Wear of Total Ankle Replacement -- Effect of Design Parameter toward wear generation -- Summary.
Keywords: Biomedical engineering; Biomaterials; Medical care; Biomedical Engineering and Bioengineering; Biomaterials; Health Care